Type 2 diabetes remission: economic evaluation of the DiRECT/Counterweight‐Plus weight management programme within a primary care randomized controlled trial. Issue 8 (16th July 2019) - Xin, Y.; Davies, A.; McCombie, L.; Briggs, A.; Messow, C.‐M.; Grieve, E.; Leslie, W. S.; Taylor, R.; Lean, M. E. J.
Abstract: Aim: The Counterweight‐Plus weight management programme achieved 46% remission of Type 2 diabetes at 1 year in the DiRECT trial. We estimated the implementation costs of the Counterweight‐Plus programme and its 1‐year cost‐effectiveness in terms of diabetes remission, compared with usual care, from the UK National Health Service (NHS) perspective. Methods: Within‐trial total costs included programme set‐up and running costs (practitioner appointment visits, low‐energy formula diet sachets and training), oral anti‐diabetes and anti‐hypertensive medications, and healthcare contacts. Total costs were calculated for aggregated resource use for each participant and 95% confidence intervals (CI) were based on 1000 non‐parametric bootstrap iterations. Results: One‐year programme costs under trial conditions were estimated at £1137 per participant (95% CI £1071, £1205). The intervention led to a significant cost‐saving of £120 (95% CI £78, £163) for the oral anti‐diabetes drugs and £14 (95% CI £7.9, £22) for anti‐hypertensive medications compared with the control. Deducting the cost‐savings of all healthcare contacts from the intervention cost resulted an incremental cost of £982 (95% CI £732, £1258). Cost per 1 year of diabetes remission was £2359 (95% CI £1668, £3250). Conclusions: Remission of Type 2 diabetes within 1‐year can be achieved at a cost below the annual cost of diabetes (including complications). Providing a reasonable proportion of remissions can be maintained over time, with multiple medical gains expected, as well as immediate social benefits, there is a case for shifting resources within diabetes care budgets to offer support for people with Type 2 diabetes to attempt remission. (Clinical Trial Registry No.: ISRCTN03267836) What's new?: Diabetes and its complications account for about 10% of healthcare budgets worldwide. The Counterweight‐Plus weight management programme in DiRECT achieved 46% remissions of Type 2 diabetes and improved cardiovascular risk factors at 1 year. One‐year incremental cost for the intervention group was estimated at £982 (95%CI £732, £1, 258) per participant compared to the control arm. Providing the DiRECT/Counterweight‐Plus intervention in primary care incurs a cost (£2359 per 1‐year diabetes remission) below the average annual direct cost of managing a person with Type 2 diabetes (including its complications), and has the potential for long‐term cost‐effectiveness. Providing that a reasonable proportion of remissions can be maintained over time, with multiple medical gains expected, and immediate social benefits, there is a case for shifting resources within diabetes care budgets to offer support for people with diabetes to attempt remission as early as possible after diagnosis.